Background Paper for Rebuilding Fiscal Institutions in Post-Conflict Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The information provided in this paper supplements the information presented in the main Board paper. The main paper discusses experiences in reestablishing fiscal management in post-conflict countries. On the basis of the Fiscal Affairs Department technical assistance recommendations to these countries, that paper identifies key priorities for rebuilding fiscal institutions in a post-conflict setting. This background paper provides more detailed information for the six selected countries-Afghanistan, Bosnia and Herzegovina, Democratic Republic of Congo (DRC), Lebanon, Mozambique, and Timor-Leste.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet